Character state variation among species of Thrips genus (Thysanoptera) in Malaysia, with one new species and two new records - Ng, Y. F.; Mound, L. A. (Zootaxa, 2020)
Thrips korbuensis sp.n. is described from a high elevated area in Peninsular Malaysia. It shares many character states with Thrips coloratus but has 8-segmented antennae and abdominal segment VIII–X uniformly dark. It also shares some features with Thrips florum, and variation in some character states used to distinguish species in the Thrips hawaiiensis group are discussed. Two species, Thrips brevistylus and Thrips subnudula, are recorded for the first time from Malaysia, and an updated checklist is provided of 27 species of the genus Thrips recorded from Malaysia.